Biological hydrogen production from Palm Oil Mill Effluent (POME) - Yeap, Shu Ying (2017)
In this study, we aim to produce biohydrogen production from POME by using indigenous hydrogen producing bacteria from POME, dark fermentation and continuously-stirred tank reactor (CSTR). Firstly, we successfully isolated four hydrogen producing bacteria, named Bacteria 1, 2, 3 and 4. We only selected Bacteria 2 as it yielded the highest percentage of biohydrogen gas. After that, the experiment was set up as shown in Figure 3.2. We also named the Bacterium 2 as JTY2017. JTY2017 was used to determine the optimum conditions to yield better hydrogen amount. The results showed the optimum condition was 35˚C and pH 5.5. The COD removal of Bacteria JTY2017 was 39%. Applications of nanoparticles (NPs) enhance bioactivity and metabolite recovery during dark fermentation and hence enhance biological hydrogen production from POME. The results obtained indicated that NPs can accelerate and increase the biohydrogen production yield in 48 hours. When the concentration of iron oxide NPs set at 4.0mg/l, the biohydrogen produced was the highest, at 76%. On the other hand, when the concentration of magnesium oxide NPs set at 4.0mg/l, the biohydrogen produced was the highest, at 71%. After that, the POMEwas sent to analyze and it showed that COD removal rate was increased too, compared to the non-NPs application. For Bacteria JTY2017 at 35˚C and pH 5.5, the POME’s COD removal with addition of iron oxide and magnesium oxide NPs was 63% and 61%, respectively. Therefore, it is shown and proved that POME has the potential to produce renewable energy, and application of nanoparticles also help to enhance the results desired.